Effects of anabolic hormones on structural, metabolic and functional aspects of skeletal muscle - Flávio de Oliveira Pires; Adriano Eduardo Lima Silva; Valmor Tricoli (Universidade Federal de Santa Catarina, 2009)
This study reviewed information regarding the effects of anabolic hormones on strength gain and muscle hypertrophy, emphasizing the physiological mechanisms that may increase muscle strength. Structural, metabolic and functional aspects were analyzed and special attention was paid to the dose-response relationship. The Pubmed database was searched and studies were selected according to relevance and date of publication (last 15 years). The administration of high testosterone doses (~600 mg/week) potentiates the effects of strength training, increasing lean body mass, muscle fiber type IIA and IIB cross-sectional area, and the number of myonuclei. There is no evidence of conversion between MHC isoforms. The interaction between testosterone administration and strength training seems to modify some metabolic pathways, increasing protein synthesis, glycogen and ATP-CP muscle stores and improving fat mobilization. Changes in 17-estradiol concentration or in the ACTH-cortisol and insulin-glucagon ratios seem to be associated with these metabolic alterations. Regarding performance, testosterone administration may improve muscle strength by 5-20% depending on the dose used. On the other hand, the effects of growth hormone on the structural and functional aspects of skeletal muscle are not evident, with this hormone more affecting metabolic aspects. However, strictly controlled human studies are necessary to establish the extent of the effects of anabolic hormones on structural, metabolic and functional aspects.